Management of balance and gait in older individuals with Parkinson''s disease. (April 2011) - Duncan, Ryan P; Leddy, Abigail L; Earhart, Gammon M
Difficulties with walking and balance are common among people with Parkinson''s disease (PD). Effective management of these walking and balance problems is critical, as these issues can contribute to decreased mobility, falls, social isolation, reduced quality of life and increased mortality. This article provides an overview of the gait and balance disorders associated with PD and discusses the methods currently utilized to manage gait and balance problems among people with PD. These methods include pharmacological, surgical and rehabilitative approaches. Remaining challenges and future directions, including the need for comprehensive, multidisciplinary, patient-centered care provided by qualified movement disorders experts, are also highlighted.